PENGARUH PROFESIONALITAS TERHADAP KUALITAS PELAYANAN PADA DINAS CATATAN SIPIL KABUPATEN PESAWARAN - Muhammad Junaidi; Fauzi Fauzi (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2020)
Given the complexity and plurality of employee conditions in the Pesawaran District Government, the Civil Registry Service employees in carrying out their duties must always improve the quality of morals, morals, faith and of course also be followed by increased professionalism and commitment based on a spirit of service based on honesty and sincerity in public services. In this case, the professionalism assessment related to these problems is seen as a social process and a communication process rather than just a psychological or econometric measurement tool, so that it will answer the question of how important the role of professionalism is to improving the service quality. The purpose of this study was to analyze the effect of professionalism on service quality at the Civil Registry Office of Pesawaran District. The results of the quantitative analysis show that partially professionalism (X1) has a significant effect on Service Quality (Y) at the Civil Registry Office of Pesawaran District. This conclusion is obtained from the Fount value obtained at 8.644, greater than the Ftable value of 3.255. While partially it is known that professionalism (X1) has a significant effect on service quality (Y) at the Civil Registry Office of Pesawaran Regency. This is shown from the t value of the professionalism variable (X1) = 2.396 which is greater than the t table value of 2.040.